Microneedle for Botulinum Toxin: A Randomized, Case-control, Single-blind Study to Assess Clinical Efficacy and Patient Satisfaction - Alberto Diaspro, MD, MSc; Silvia Silenzi, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Lateral canthal lines can be effectively treated with injections of botulinum toxin, whereas the aesthetic effects can vary due to factors such as injection depth, which is essential for achieving predictable clinical outcomes. Microneedles (MNs) have proven effective in intradermal skin rejuvenation procedures. However, a comparison of their performance with traditional needles is still lacking in the scientific literature to reliably evaluate their efficacy. This study is therefore aimed to evaluate the clinical efficacy and patient satisfaction of botulinum toxin A injected intradermally using a standard needle versus an MN device. Methods:. Twenty recruited participants received a single injection of 10 Speywood Units (US, 0.05 mL) for each of the six standard points (total dose: 60 US) at T0 using both the control needle and the MN, randomly assigned. Follow-up visits were scheduled at 30 (T1) and 90 (T2) days, along with patients and blind observer evaluation of the clinical improvement of periocular wrinkles. Results:. The measurement of wrinkle depth showed that MN injection had similar efficacy to a normal needle, whereas blind evaluation indicated better results for the MN. Patient subjective assessments of procedure pain/discomfort and likelihood of repeating the procedure also favored the MN. Conclusions:. This pilot study suggests that the MN device holds promise for optimizing the clinical results of botulinum toxin injections by controlling injection depth and enhancing patient acceptance and injection experience compared to standard needle injection. The absence of adverse events further supports the efficacy of MN for intradermal botulinum toxin use.